G85(P) Do site and pattern of ear bruising assist in determination of non-accidental or unintentional injury. (24th May 2017) - Khera, RS; Teebay, L; Gladstone, M; Allen, M
Abstract : Aim: To describe the features (demographic, history, and investigations) of non-accidental injury (NAI), unintentional, and unexplained ear bruising in children over a 10 year period (2006– 2016) at Alder Hey Children's NHS Foundation Trust, Liverpool, UK, and to ascertain if there is a correlation between aetiology of bruising, specific anatomical site and pattern of ear bruising. Methods: A retrospective case review of all case notes (initially 4480 cases for the 10 year period), with identifiers linked to 'external ear bruising' (specifically requested on auditing of all case notes), recorded in a database which included all admissions into the Rainbow Centre at Alder Hey Children's NHS Foundation Trust, was conducted. This included auditing images of the affected areas. Data including demographics, aetiology of bruise, history, mechanism of injury, anatomical site, type of bruise, location of other body injuries, investigations, and case outcome were recorded on a proforma. Results: 29 cases of ear bruising were identified; 76% were males and 79% were children aged 1 to 5 years old. The distribution of bruises over each ear was similar (55% right ear) with 9 bilateral cases. The commonest aetiology was unexplained (45%). Unintentional bruising had various causes: from mechanical to selfinfliction. NAI cases of ear bruising are most likely to present in 3–6-year-old male children who are mobile. NAI cases presented with at least 3 ear bruises, typically around the scaphoid fossa (under the helix) or on the posterior surface. Unintentional ear bruising cases were most likely to present in 2–3-year-old children who were mobile and showed bruising typically around the upper anterior helix. Overall, most children had no social service involvement (55%), and were referred originally through nursey or school (52%) as an unwitnessed history (55%). Conclusion: A child with NAI ear bruising is more likely to have NAI bruising on another part of their body. Educational institutions play a key role in identifying injuries. Further research across different settings with a larger number of cases is encouraged to build on these initial findings.